Students’ and lecturers’ perceptions towards e-learning in higher education - Maya Marsevani; Rika Al Fitri (Universitas Islam Malang, 2023)
This research determines the perceptions of students and lecturers on using e-learning at a private university in Batam. A mixed methods approach was employed to find out these perceptions. Researchers further collected the data through open and closed questionnaires from 243 students (2019-2022 school year) and 19 lecturers who were actively teaching and using e-learning. After obtaining the data, the questionnaire results were calculated using SPSS software version 25 and transcribed qualitatively. The results show that students and lecturers had positive perceptions towards e-learning. This is measured by the knowledge, adaptation, benefits, and attitudes of students and lecturers in using e-learning. However, several obstacles were faced by them, such as time management, difficulties in accessing the e-learning website, the user interface (UI) display is quite complicated, unsupported internet signal, and others. It can be concluded that both lecturers and students have good ability in using e-learning at higher education levels.